Var Gene Encoding Duffy-Binding Like (DBL) 1α- Plasmodium Falciparum Erythrocyte Membrane Protein 1 (PfEMP1) as Diagnostic Marker and Clinical Predictor Candidates for Falciparum Malaria - Dewi, Rosita; Sulistyaningsih, Erma; Aprilia, Annisa Nadya; Kusuma, Irawan Fajar; Sillehu, Sahrir (Althea Medical Journal, 2024)
Background: The pathogenesis of severe malaria involves the antigenic protein Plasmodium falciparum erythrocyte membrane protein-1 (PfEMP1), encoded by the var gene. One of the important domains in PfEMP1 is Duffy Binding Like 1α (DBL1α). To diagnose malaria, microscopic examination has low sensitivity and specificity, therefore, the development of molecular-based methods is needed. This study aimed to determine the potential of DBL1α-PfEMP1 as a diagnostic marker and clinical predictor for falciparum malaria.Methods: An exploratory descriptive study was conducted in 2019 on malaria patients at the Tiakur public health center, Southwest Maluku, Indonesia. Blood samples of patients infected with Plasmodium falciparum malaria were collected on filter paper for DNA isolation. Amplification by polymerase chain reaction (PCR) method used primers αAF [5'-GCA CG(A/C) AGT TTT GC-3'] and αBR [5'-GCC CAT TC(G/C) TCG AAC CA-3'] with cycles of denaturation 95oC 1-minute, annealing 42oC 1-minute, elongation 60oC 1-minute. PCR products were electrophoresed using 1% agarose gel. Amplicons were sequenced directly and analyzed using nucleotide BLAST-NCBI. Results: All patients showed mild malaria symptoms. PCR amplification yielded bands of 370 bp in all samples and 600 bp in 8 out of 10 samples, and 1 sample had a different pattern. Sequencing results confirmed that the amplicon was DBL1α, a var gene that had similarities to sequences from other regions.Conclusion: Positive amplification and sequencing results confirm the sensitivity of DBL1α-PfEMP1 as a diagnostic marker. The sequence variability of PCR product implies the presence of DBL1α variations, indicating a correlation with clinical outcomes and making it a clinical predictor.